Difficulties in the teaching-learning process within the classroom and influence of ICT to minimize them (2019)
Currently, the methodologies that implement the use of information technologies favor the teaching-learning processes in one way or another. This research analyzes some of the problems detected in the teacher-student interaction within the classroom and the support social networks and information technologies have given to minimize them. Finally, the use of ICT in the teaching process is introduced, citing specific examples of implementation of new methodologies, such as M-learning, e-learning, and the different tools used to help counteract these problems